Application of the magnetic fluid as a detector for changing the magnetic field; IOP Conference Series: Materials Science and Engineering; Vol. 363 : Cognitive Robotics - Zyatkov D.; Yurchenko A. V. Aleksey Vasilievich; Yurchenko V.; Balashov V. (2018, 2018)
Title screen